Ação farmacológica de Syzygium cumini (L.) skeels - Migliato, Ketylin F. [UNESP]; Baby, André R.; Zague, Vivian; Velasco, Maria Valéria R.; Correa, Marcos Antonio [UNESP]; Sacramento, Luis V. S. [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (My University, 2006)
Natural products have received new interest recently, maybe in men's attempt to turn into the nature for the prevention and the relief of diseases, mainly because of those untreated by the traditional medicine. Syzygium cumini (L.) Skeels, popularly known as 'jambolão, is a well-known plant by several pharmacological actions so much in the popular use as in the scientific literature. In this search antidiabetic, anti-diarrhoeal, anti-inflammatory, antioxidant and antimicrobial activities of 'jambolão' were described, among other actions.
Pharmacological action of Syxygium cumini (L.) skeels
Keywords: 'Jamelão'; Black plum; Myrtaceae; Pharmacological action; Syzygium; antiinflammatory activity; antimicrobial activity; antioxidant activity; drug mechanism; nonhuman; plum; scientific literature; Syzygium cumini